PERAN DAN MANFAAT SIA DALAM PENENTUAN STRATEGI PENJUALAN PRODUK PADA E- COMMERCE - Elmiano Artanto Epot Erong; Hwihanus Hwihanus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The use of electronic media in generating income is a new method that has been intensively applied by many business actors recently. The use of electronic media in buying and selling transactions is better known as E-commerce. The media used in E-commerce, of course, very much depends on which media is considered the easiest to use by the party concerned. Because product marketing is being intensively carried out by many business actors, the competition in E-commerce is quite large and, as usual, those who are unable to compete will lose and are ready to bear losses. the most creative and innovative strategies in marketing products in every e-commerce that way, the products offered are still considered by consumers. As for determining this strategy, one of the most appropriate things to do is to use or implement an accounting information system (SIA). In simple terms, SIA can be interpreted as a system whose job is to prepare information obtained from collecting and processing transaction data that is useful for all users, both internal and external parties of the company.